Revealing students' emotional engagement in class: An online distance learning (ODL) perspectives / Faddliza Mohd Zaki ... [et al.] - Mohd Zaki, Faddliza; Nasharudin, Nurhidayah; Shafie, Zailani; Abu Hassan, Amirah; Hussin, Muhammad Noor; Mohd Zaid, Noor Azila (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Online Distance Learning (ODL) is a prominent method used in conducting online class for institutions of higher learning (IHLs) in Malaysia since COVID-19 pandemic. Therefore, it is vital to understand students' emotional engagement during online class to improve learning. This study focuses on university's students' preference in participating during online class and their emotional reactions by identifying their positive or negative feelings toward online class participation. A quantitative method was used and questionnaire was addressed to 163 Information Science Studies students from College of Computing, Informatics and Mathematics, Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, Rembau Campus. The results showed that 65.6% of students prefer to participate actively during online class with positive feelings as revealed by the study where 17.8% students enjoy being acknowledged and feels appreciated if lecturer call upon their name in class to share their opinions and ideas or answer questions given to them. In addition, 14% students stated this action can boost their confidence and enhance their communication skills. These findings are in line with previous research that showed interpersonal relationships and interaction between students and lecturers have a pivotal role in inducing students' confidence and involvement. Active communication between lecturers and students can promotes students' sense of belonging which make them more interested in capturing the information and knowledge convey in class. Hence, the findings may spark interests for lecturers or educators to engage students learning so active learning session can be developed and benefits both parties. Thus, may give positive influence on lecturers-students relationship.